Developing a face-shear lead-free piezoelectric transducer through anti-parallel co-poling and its application to an omnidirectional piezoelectric transducer. Issue 5 (1st March 2023) - Eum, Jae-Min; Kim, Eun-Ji; Kim, Dae-Su; Go, Su-Hwan; Chae, Yeon-Gyeong; Lee, Dong-Gyu; Kim, Seung Il; Choi, Yong Rak; Choi, Wonjae; Ha, Jong Moon; Seung, Hong Min; Nahm, Sahn
Abstract: Face-shear deformation was observed in various square piezoelectric transducers prepared using the anti-parallel co-poling method, which led to uniform polarization and the generation and receipt of pure fundamental shear horizontal (SH0 ) waves without any Lamb wave. The amplitude of the SH0 wave was found to be proportional to the piezoelectric charge constant ( d 33 ) of the piezoceramic, suggesting that the d 33 value can be used as a figure of merit for piezoelectric transducers with strong SH0 waves. The amplitude of the SH0 wave associated with the square piezoelectric transducer is large at 0° and 90° but almost zero at 45°; therefore, a piezoelectric transducer with good omnidirectional properties needs to be developed. A ring-type omnidirectional piezoelectric transducer was produced using eight trapezoidal piezoceramics. The minimum amplitude of the SH0 wave generated and received by the ring type-transducer exceeded 70% of the maximum amplitude. Hence, this ring-type transducer is highly omnidirectional and can be used for nondestructive testing and structural health-monitoring applications.